LINGUISTIC STUDY OF PHRASEOLOGICAL UNITS EXPRESSING COLOR IN ENGLISH AND UZBEK LANGUAGES - Umarqulova, Maxliyo (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This study conducts a comparative analysis of phraseological units expressing color in English and Uzbek languages, aiming to uncover linguistic and cultural intricacies embedded within these expressions. Through systematic data collection, selection, and analysis, we elucidate semantic structures, metaphorical extensions, and cultural connotations associated with color-related phraseology in each language. In English, a plethora of idiomatic expressions reflect the pervasive influence of color symbolism, while Uzbek phraseology emphasizes natural phenomena and cultural motifs. Contrastive analysis reveals both cross-linguistic universality and language-specific nuances in color representation. Our findings underscore the dynamic interplay between language, culture, and cognition in shaping perceptions of color. This research contributes to a deeper understanding of linguistic diversity and cultural identity, highlighting the significance of phraseological analysis in uncovering the intricate nuances of language and culture.